ANALISIS PERSEPSI DAN HUBUNGAN PRESTASI BELAJAR MATEMATIKA DENGAN PRESTASI BAHASA PEMROGRAMAN - Herlina, Herlina; Surya Mulyana, Teady Matius (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2019)
Mathematics is the basis before learning coding-based courses. This type of research is quantitative descriptive. Sample of 110 informatics engineering students. The results of the study showed a significant association of learning outcomes in mathematics with the achievement of learning programming languages. The magnification coefficient of 0.663 has a moderate and positive meaning. The contribution of mathematics in explaining programming languages ??is 43.97% and the remaining 56.03% is accepted by other variables. Students' perceptions of mathematics and programming languages ??consist of four levels of understanding, namely the five senses, analysis, interpretation and evaluation. Every level of dimension. On the sensory dimension of 31.9% mathematics has a close relationship with programming languages. In the dimensions of analysis and interpretation, the value of the percentage of perceptions that are almost the same namely 21.24% and 21.14% associate mathematical concepts with the concepts of programming languages. In the evaluation dimension of 20.6%, it shows that in programming languages, students need information other than mathematics, namely the purpose of the programming language that is being designed.